The Discovery Learning Activities of "Science is Fun" Program of Kompas TV to Teach English for Young Learners - Dzikri Fajriyah, Annahdhi; Wahyuni, Erly (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2014)
The Discovery Learning Activities of "Science is Fun" Program of Kompas TV to Teach English for Young Learners